The e-Portfolio: a systematic review of the Italian educational research - Ludovica Fanni (Firenze University Press, 2023)
The paper displays a systematic analysis of the national literature found within journals in the 11/D2 field on the topic of the e-Portfolio. The goal is to explore how much, and in what ways, research has discussed the topic over the past two decades. The selection criteria adopted led to the identification of 24 publications from which a descriptive process of the uses and needs related to this tool was carried out. It emerges that the reasons why this tool is used are various, although it is not widely exploited in education outside the probationary year for newly hired teachers.   L'e-Portfolio: una revisione sistematica della ricerca educativa italiana. Il contributo espone un'analisi sistematica della letteratura nazionale presente all'interno delle riviste del settore 11/D2 sul tema dell'e-Portfolio. L'obiettivo è quello di esplorare quanto e con quali focus la ricerca abbia discusso sul tema nell'ultimo ventennio. I criteri di selezione adottati hanno portato all'individuazione di 24 pubblicazioni a partire dalle quali è stato portato avanti un processo descrittivo degli usi e delle necessità legate a questo strumento. Ne emerge che le intenzioni per le quali si opta per l'utilizzo di tale strumento sono plurime, anche se non viene ampiamente sfruttato in ambito formativo al di fuori dell'anno di prova dei docenti neoassunti.